1980
DOI: 10.1042/bj1910681
|View full text |Cite
|
Sign up to set email alerts
|

The antibody response to myoglobin is independent of the immunized species. Analysis in terms of replacements in the antigenic sites and in environmental residues of the cross-reactions of fifteen myoglobins with sperm-whale myoglobin antisera raised in different species

Abstract: The recent determination of the entire antigenic structure of sperm-whale myoglobin with rabbit and goat antisera has permitted the examination of whether the antigenic structure recognized by antibodies depends on the species in which the antisera are raised. Also, by knowledge of the antigenic structure, the molecular factors that determine and influence antigenicity can be better understood in terms of the effects of amino acid substitutions occurring in the antigenic sites and in the environmental residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 48 publications
(49 reference statements)
5
23
0
Order By: Relevance
“…A second donor (donor 63) had a noteworthy reactivity to sperm whale myoglobin. This may reflect a bona fide cross-reactive antibody, since humans are known to have circulating anti-myoglobin antibodies (8,9), and cross-reactivity between anti-myoglobin antibodies and myoglobins from a variety of species is not unusual (25). Additional experiments in this validation exercise included serial dilution of the human positive control serum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A second donor (donor 63) had a noteworthy reactivity to sperm whale myoglobin. This may reflect a bona fide cross-reactive antibody, since humans are known to have circulating anti-myoglobin antibodies (8,9), and cross-reactivity between anti-myoglobin antibodies and myoglobins from a variety of species is not unusual (25). Additional experiments in this validation exercise included serial dilution of the human positive control serum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that the same five antigenic sites on sperm-whale Mb are recognized by rabbit and goat antisera [l] and by chicken, cat, pig, and mouse antisera [46]. Also, rabbit, goat, cat, and mouse antisera recognize the same three antigenic sites on lysozyme [4, 951.…”
Section: Structurally Inherent Antigenic Sitesmentioning
confidence: 99%
“…Recently, we studied the immunochemical cross-reaction of 15 myoglobins at the antibody level in several outbred species of animals 1461 and in selected inbred mouse strains both at the antibody level 1521 and by the T-cell proliferative response [114]. The findings have shown that the immunochemical cross-reactions can be reasonably rationalized on the basis of amio acid substitutions occurring in the residues of the antigenic sites and in the environmental (nearest-neighbour) residues surrounding the sites [46]. Frequently, one-removed or even more distant residues from the sites exerted some effects.…”
Section: Effects Of Amino Acid Substitutions On Antigenic Sitesmentioning
confidence: 99%
“…Also, the binding to AChR peptide of antibodies against unrelated proteins served as additional controls. Antibody binding was determined by a double-antibody assay [28] using 1251-labelled rabbit and mouse IgG to monitor the binding of unlabelled mouse anti-AChR antibodies.…”
Section: Adsorbent-binding Studiesmentioning
confidence: 99%